'Saying no to organ donation': an empirical typology of reluctance and rejection. Issue 8 (28th June 2018) - Pfaller, Larissa; Hansen, Solveig L.; Adloff, Frank; Schicktanz, Silke
Abstract: In Germany, as well as in other countries, organ shortages are usually explained by a relative unwillingness to donate among a population which is assumed to be caused by a lack of information and mistrust of the system. As we can see in the data of our qualitative research (focus groups and interviews), lack of information or mistrust are not the only reasons for people to be reluctant to agree to the donation of their organs after death. In fact we can identify four positions: (1) information deficit; (2) mistrust; (3) no killing; and (4) bodily integrity. The first and second are the two prominent explanations in the public discourse about low donation rates. The third and the fourth instead have neither been adequately articulated nor been discussed as a proper argument. Therefore, by means of sociology of critique, we discuss their contribution to the discourse as comprehensible reasons for reluctance and present them as credible positions of criticism: These two positions illuminate fundamental and universal values of the inviolability of the person and human dignity. Thus, both positions are consistent and morally justifiable and should be addressed with sensitivity.